The first eclipsing binary catalogue from the MOA-II data base. Issue 1 (23rd May 2017) - Li, M. C. A.; Rattenbury, N. J.; Bond, I. A.; Sumi, T.; Bennett, D. P.; Koshimoto, N.; Abe, F.; Asakura, Y.; Barry, R.; Bhattacharya, A.; Donachie, M.; Evans, P.; et al.
Abstract: We present the first catalogue of eclipsing binaries in two MOA (Microlensing Observations in Astrophysics) fields towards the Galactic bulge, in which over 8000 candidates, mostly contact and semidetached binaries of periods <1 d, were identified. In this paper, the light curves of a small number of interesting candidates, including eccentric binaries, binaries with noteworthy phase modulations and eclipsing RS Canum Venaticorum type stars, are shown as examples. In addition, we identified three triple object candidates by detecting the light-travel-time effect in their eclipse time variation curves.